Fit for purpose? OrganisationaL prOdUctivity and woRkforce wellbeIng in workSpaces in Hospital (FLOURISH): a multimethod qualitative study protocol. Issue 4 (20th April 2019) - Rapport, Frances; Auton, Emilie; Cartmill, John; Braithwaite, Jeffrey; Shih, Patti; Hogden, Anne; Clay-Williams, Robyn
Abstract : Introduction: Workspaces are socially constructed environments where social relationships are produced, reproduced, challenged and transformed. Their primary function is to support high-quality service delivery to the benefit of 'patients'. They are also settings where employees can work effectively, in a safe and healthy environment, delivering a high-quality service according to a 'Work-As-Done' rather than a 'Work-As-Imagined' model. However, hospital design is currently based on a managerial understanding of work accomplishments, often falling short of understanding what is actually happening on the ground. Furthermore, the research landscape lacks rigorous assessment of these complex sociological and health research concepts, either within the Australian context where this protocol is set, or internationally. This paper describes an innovative protocol aimed at examining healthcare employees' and organisations' concerns and beliefs in workspace design. It outlines research investigating the effect of workspace use on productivity, health and safety and worker satisfaction, to clarify Work-As-Done, while creating healthy and more fulfilling environments. Methods: This is a proof-of-concept study, taking place between June 2018 and April 2019, employing a multimethod, qualitative approach for in-depth assessment of one Australian, private, university hospital environment, using as its 'case' the Gastroenterology Surgical Unit. It involves (1) observations and informal interviews (shadowing) with employees and patients as they traverse hospital spaces and (2) visual data of spatial use. Fieldnotes will be analysed thematically, and visual data analysed using a predefined schematic framework (a visual taxonomy). Overarching themes and categories will be considered corroboratively, mixing visual and textual data to build an iterative and dynamic picture. Ethics and dissemination: Ethical considerations will be discussed, while approval has been granted by the University's Human Research Ethics Committee (HREC/5201800282), along with Governance approved by the Health Clinical Research Executive (CRG2018005). Study results will be disseminated through publications, research conferences and public reports.